Time management v práci stavebního manažera - Jirátková, Marie (Vysoké učení technické v Brně. Fakulta stavební, 2019)
Cílem této diplomové práce je zjistit, zda manažer ve stavebnictví využívá ke svému plánování metody time managementu. Teoretická část práce začíná základním vymezením pojmu time managemet, stanovením cílů a priorit, jaké metody time managemet využívá a jak ho dobře zvládnout. Zabývá se i stinnou stránkou prokrastinací, jako nezvládnutím time managementu. Zabývá se vysvětlením metod time managementu a také jejich historií. Druhá, prakticky zaměřená část obsahuje navržené hypotézy, které zkoumají, jak je time management ve skutečnosti stavebními manažery využíván, jak mu napomáhá elektronika a zda manažeři upřednostňují pracovní čas. Autorka se určené hypotézy snaží potvrdit či vyvrátit, pomocí dotazníkového šetření a řízenými rozhovory ve vybraných stavebních firmách. Výsledkem diplomové práce jsou vhodná doporučení pro efektivnější plánování času a vyvarování se chyb v této oblasti.

The goal of the thesis is to find out if manager in the area of building uses the methods of time management for the planning of work and tasks. At the beginning of theoretical part is the basic definition of the „time management“, assessment of the goals and the priorities, explanation of the methods used by time management and how to manage effectively. This part of the thesis deals with the downside as well – procrastination. Shows this downside as inability to manage the time management. The methods of time management are described and history of this methods as well. The second – practical part of the thesis – contains proposed hypotheses what investigate how the time management is in reality used by building managers, how helps the electronics and if managers prefer the working time. The author tries this hypotheses to confirm or to refute using the survey and structured interviews in selected building companies. The results of the thesis are suitable recommendations for more effective planning of the time and avoidance the mistakes in this area.
Time management in construction company managerial work
Keywords: Stavebnictví; manažer; Time management; metody; čas; prokrastinace; construction; manager; Time management; methods; time; procrastination